Kearifan Lokal Sumba Timur Dalam Tradisi Cium Hiung (Papuduk) Sebagai Sumber Media Pembelajaran Sosiologi Di SMA Negeri 1 Nggaha Ori Angu - Faizah Ulumi Firdausi; Yanus Ndunu Tura Amah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Sumba Island is an island located in East Nusa Tenggara Province which is known for its rich culture and traditions because many cultures are passed down from generation to generation from the legacy of their ancestors. The people of East Sumba are a society that is rich in culture, and has all kinds of traditions that are carried out from generation to generation, namely one of them, "papuduk" this tradition is very unique because at every event or encounter between kinship, relatives, or people from outside visiting the area the community East Sumba will definitely greet and embrace the person to kiss "papuduk" regardless of type or status, because it is a sign of respect for the people of East Sumba, symbolizing sincerity and honesty between us and other people. Likewise at SMA N.1 Ngaha ori angu where they apply this tradition in relation to sociology learning media, namely one of them interacts with each other, every time a high school meeting is sure to follow the "papuduk" tradition, namely as a sign of mutual care or a sense of mutual respect each other.